The role of film in environmental communication: An audience interpretation in Indonesia and Malaysia - Briandana, Rizki; Mohamad Saleh, Mohamad Saifudin; Dwityas, Nindyta Aisyah (Fakultas Dakwah dan Komunikasi Universitas Islam Negeri Walisongo Semarang, 2024)
Film is a form of communication that has the power to persuade viewers to alter their perceptions and actions in order to support the communicator's chosen media agenda. Politics is the topic that is frequently covered in movies. In the documentary The Years of Living Dangerously, the topic of global warming is viewed from the angle of societal issues, offering a fresh perspective to the audiences. The issue of environmental destruction that took place all across the world served as the theme. The concern highlighted in the movie is that its magnitude has significantly increased global greenhouse gas emissions. Deforestation in Indonesia and Malaysia was one of the topics brought up. This study aims to analyze the audience's interpretation of the role of film in communicating environmental communication. This study used the reception analysis method with the FGD data collection technique. The informants in this study are audiences in Indonesia and Malaysia. The results of this study indicate that environmental communication in Indonesia and Malaysia which discuss deforestation issues are interpreted by the public as part of social problems that are difficult to control. Meanwhile, the government is framed as a political communicator that is not transparent, causing public distrust.*****Film merupakan salah satu bentuk komunikasi yang memiliki kekuatan untuk membujuk pemirsa agar mengubah persepsi dan tindakannya guna mendukung agenda media yang dipilih komunikator. Politik adalah topik yang sering diangkat dalam film. Dalam film dokumenter The Years of Living Dangerously, topik pemanasan global dilihat dari sudut pandang isu-isu kemasyarakatan, sehingga menawarkan perspektif baru kepada penontonnya. Isu kerusakan lingkungan yang terjadi di seluruh dunia menjadi tema yang diangkat. Kekhawatiran yang disoroti dalam film ini adalah besarnya dampak buruk ini telah meningkatkan emisi gas rumah kaca global secara signifikan. Deforestasi di Indonesia dan Malaysia menjadi salah satu topik yang diangkat. Penelitian ini bertujuan untuk menganalisis interpretasi penonton terhadap peran film dalam mengkomunikasikan komunikasi lingkungan. Penelitian ini menggunakan metode analisis resepsi dengan teknik pengumpulan data FGD. Informan dalam penelitian ini adalah khalayak di Indonesia dan Malaysia. Hasil penelitian ini menunjukkan bahwa komunikasi lingkungan hidup di Indonesia dan Malaysia yang membahas isu deforestasi dimaknai oleh masyarakat sebagai bagian dari permasalahan sosial yang sulit dikendalikan. Sementara itu, pemerintah dibingkai sebagai komunikator politik yang tidak transparan sehingga menimbulkan ketidakpercayaan masyarakat.